EFFECT OF LEADERSHIP FUNCTION AND WORK MOTIVATION TOWARD EMPLOYEE PERFORMANCE IN THE ENVIRONMENT OF PT. SUBUR JAYA KARAWANG - Jamaludin, Asep; Firmansyah, Yudi (International Journal of Psychosocial Rehabilitation, 2020)
The achievement of an organization is greatly influenced by the individual performance of its employees. Low performance of subordinates is usually influenced by the low role of superiors in developing humane communication and provide learning to subordinates. And the lack of motivation from superiors to subordinates for discipline and not being lazy. Low employee morale, and reduce employee performance due to lack of motivation given and shown by superiors and work motivation that is rarely given by leaders. A superior’s leadership function is very influential on employee performance in supporting the achievement of organizational goals. A superior in leading a formal organization must have a strong character in order to be able to lead his subordinates in the form of a good personality, intellectual and skills related to his field of expertise in order to build human resources, especially his subordinates. As mentioned by Saydam, 1996, every activity that starts with the stages of planning, organizing, actualizing, controlling and controlling all of these are all aimed at achieving the company’s objectives in a planned manner.